Serum β-hCG Levels as a Predictive Marker for Gestational Hypertension: A Cross-Sectional Study at Major Shabbir Sharif Hospital, Kunjah, Pakistan - Saiqua Muneer, Ghazala Iftikhar, Shazia Sultana, Aneela Nadeem, Areesha Kamran, Saba Abrar, Muhammad Jamal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pregnancy-induced hypertension (PIH) is a serious obstetric condition that can have adverse maternal and fetal outcome. The aim of this study was to investigate the relationship between early second trimester β-hCG levels in the circulation and the risk of developing PIH, evaluating its potential as an early predictive biomarker. Materials and Methods: A cross-sectional study was conducted at Major Shabbir Sharif Hospital in Kunjah, Pakistan between November 2021 and December 2022. We enrolled 100 normotensive pregnant women aged 20–40 years at 14–19 weeks gestation. Participants were categorized based on age, socioeconomic status, and occupation. Serum β-hCG levels were measured alongside routine blood pressure monitoring. Statistical analysis assessed correlations between β-hCG levels and subsequent PIH development. Results: The study included 100 pregnant women with a mean age of 27.6 years, of whom 39% developed PIH classified as mild (33%), moderate (44%), or severe (23%). Early second trimester serum β-hCG levels showed a clear relationship with PIH severity, rising from 2.10 MoM in mild cases to 3.60 MoM in moderate and 4.40 MoM in severe PIH (p < 0.001). Clinical markers of disease progression, including pedal edema (64%) and proteinuria (46%), were significantly associated with higher β-hCG levels (3.80 MoM and 4.10 MoM, respectively). Notably, while PIH cases spanned all age groups, the majority occurred in women under 30 (74%), with higher prevalence among housewives (65%) and lower socioeconomic groups (40%), suggesting demographic-specific risk patterns in this population. Conclusion: Second-trimester β-hCG elevation strongly correlates with PIH risk and severity, suggesting its utility as an early predictive marker. Incorporation of β-hCG screening in prenatal care protocols could enable timely interventions to improve perinatal outcomes. Keywords: Pregnancy-Induced Hypertension, β-hCG, Early Prediction, Maternal Health, Fetal Outcomes.